C-reactive protein in atherosclerosis – A risk marker but not a causal factor? A 13-year population-based longitudinal study: The Tromsø study. (August 2017) - Eltoft, Agnethe; Arntzen, Kjell Arne; Hansen, John-Bjarne; Wilsgaard, Tom; Mathiesen, Ellisiv B.; Johnsen, Stein Harald
Abstract: Background and aims: CRP predicts cardiovascular disease (CVD) in large epidemiologic studies. The aim of the present study was to elucidate the role of CRP in atherosclerosis formation and progression in a prospective population-based study. Methods: 6503 middle-aged subjects from The Tromsø study had serum CRP, carotid ultrasound and complete covariate data collected at baseline in 1994. Of these, 4730 and 2917 attended follow-up surveys with repeated assessments in 2001 and 2007, respectively. The cross-sectional associations between CRP and subclinical carotid atherosclerosis, and the longitudinal associations between baseline CRP and novel plaque formation and plaque progression were assessed in generalized estimating equations and linear mixed models stratified by sex. Results: At baseline, traditional risk factors and plaque prevalence increased by CRP risk categories (<1 mg/L, 1–3 mg/L, and >3 mg/L) in both sexes. In cross-sectional analyses, multivariable-adjusted CRP was associated with plaque prevalence and total plaque area (TPA) in men and women. Age-adjusted baseline CRP >3 mg/L compared to CRP <1 mg/L predicted novel plaque formation (OR 1.44, CI 1.08–1.92) and TPA progression (β = 0.0.029 (CI, 0.003–0.056)) in men, but not in women. In neither men nor women was baseline CRP a predictor of TPA-progression or novel plaque formation when adjusted for traditional risk factors. Conclusions: CRP was associated with plaque presence and TPA in cross-sectional analyses, but was not an independent predictor of novel plaque formation or plaque progression. Our findings suggest that CRP may link to CVD by other mechanisms than promoting formation and progression of atherosclerotic plaques. Highlights: CRP and carotid atherosclerosis are cross-sectionally associated. Associations are attenuated, but remain significant when adjusted for CVD risk factors. Age-adjusted baseline CRP predicts plaque formation and plaque progression in men. CRP did not predict plaque formation or progression upon multivariable adjustment. CRP may be a tool to identify subjects with prevalent atherosclerosis.